Assessment and Mapping of Wind Erodibility of Aridisols and Entisols in the Red Sea State, Sudan* (University of Khartoum Journal of Agricultural Sciences, 2023)
Wind erodibility of a soil (WE) is a major indicator of itssusceptibility to wind erosion under a given climatic condition. This studyis part of a national project for assessing and mapping wind erodibility ofsoils in Sudan. It was undertaken to generate WE data for the Red SeaState. Three replicate surface soil samples were collected, randomly, fromtwenty-eight geo-referenced farms spread in the State. Non-erodible soilparticles (NEP>0.84mm) and selected soil properties were measuredusing standard procedures. The mean NEP values ranged from 17.0% to57.2% with an overall mean coefficient of variation of replicatedeterminations equal to 4.7%. The equivalent WE ranged from 49.6 to244.0 ton/ha. The results showed a highly significant (P
Keywords: Soil erodibility; wind erosion; Red Sea State